The Intervention Effect of Warm Blanket Compresses and Essential Aromatherapy on Increasing the Body Temperature of Surgical Patients - Zakaria, Prima; Pujiastuti, Rr. Sri Endang; Mardiyono, Mardiyono (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: This study aimed to show the effectiveness of a combination of interventions by providing warm compresses, blankets, and essential aromatherapy to determine changes in the patient's body temperature after surgery Methods: The research design used accurate experimental research with a pretest-posttest design. This study had 60 respondents divided into two groups, using a non-probability sampling technique with a stratified random sampling method. The control group was given intervention according to standard hospital procedures: a Striated Blanket at room temperature. The intervention group was given a combination of warm compresses and warm blankets. The temperature of the warm blanket is 44 Celsius, with a compressive time of about 30 minutes. Essential aromatherapy is four drops in 100 cc of water with diffusion for 15 minutes. The research was conducted from December 26, 2022, to January 28, 2023 Results: This research shows a significant difference in the average increase in body temperature. After intervention treatment, a significant value was obtained, namely with a pre-value of 35.43°c and a post-value of 36.50°c (p=0.00). Combining a warm compress with a warm blanket at a temperature of 44 Celsius for 30 minutes and giving essential aromatherapy four drops in 100 cc of water with diffusion for 15 minutes give a significant result for body temperature. Conclusion: The combination of warm compresses, warm blankets, and essential aromatherapy effectively increases the body temperature of postoperative spinal anesthesia patients in the recovery room.